Pemerian polisemi "datang": satu analisis linguistik kognitif (Jurnal Bahasa, 2005)
Polysemy - a multiple but related meanings for a single form - poses a problem in semantic theory and the semantic applications such as lexicography, translation and natural language processing system. In lexi-cographic practice, there is no objective criteria for the analysis and the treatment of a polysemous word. This study explores lexical polysemy through an in-depth examination of a Malay simple stem verbs: datang. Working within a cognitive linguistic framework, the present study shows that this polysemous word is systematically and radially structured. Its subsenses are derived from a core sense. The senses are non-arbitraly but they are shown in their well-motivated interrelations through the conceptual metaphor and metonymy projections and the image-sche-matic transformations. The study has made an attempt to use this highly organised semantic network as a basis for the arrangement and treat-ment of meaning of this polysemous headword in the dictionary